Metabolic Syndrome Spectrum in Children with Classic Congenital Adrenal Hyperplasia—A Comprehensive Review - Sanja Panic Zaric; Tatjana Milenkovic; Sladjana Todorovic; Katarina Mitrovic; Dimitrije Cvetkovic; Maja Cehic; Jelena Vekic; Katja Dumic; Rade Vukovic (Metabolites)
Children with a classic form of congenital adrenal hyperplasia (CCAH) have a potentially increased risk of unfavorable cardiometabolic events due to the interplay of corticosteroid treatment, hyperandrogenism, and other factors. Although readily recognized in adults, these aspects are frequently overlooked in children and youth with CCAH; Aim: To review the evidence available from studies regarding cardiometabolic health outcomes in CCAH patients; Methods: A review of the literature was performed following PRISMA guidelines, including studies published between 2000 and 2024. We included studies reporting cardiometabolic outcomes in children and adolescents (<18 years) with CCAH. Where pediatric data were sparse, additional data were obtained from studies with older adolescents and young adults (15–25 years). Cardiometabolic outcomes included risk factors, such as obesity, insulin resistance, lipids, blood pressure, and vascular markers; Results: Twenty-five studies were analyzed. The prevalence of obesity was found to be higher in children with CCAH, as well as of increased visceral adiposity. Higher indices of insulin resistance were also a frequent finding in children with CCAH. CCAH patients had higher systolic blood pressure and more frequently loss of nocturnal blood pressure dipping, particularly among salt-wasting subtypes and in younger children. Subclinical atherosclerosis was indicated by increased carotid intima–media thickness, elevated hs-CRP, and impaired endothelial function. Other findings suggested changes in lipid profiles, particularly decreased HDL-c and increased triglycerides, although the findings were less consistent; Conclusions: Compared with the general pediatric population, children with CCAH were found to have an increase in multiple cardiometabolic risk factors. It is therefore vital to monitor these risk factors in pediatric CCAH, as well as tailoring treatment with cardiometabolic health in mind, to achieve better long-term cardiovascular and metabolic outcomes. Future research should focus on longitudinal studies of cardiometabolic outcomes and innovative therapeutic approaches to reduce these risks in patients with CCAH.